Swagger/OpenAPI Specification as a Governance Tool for Internal Data Products: Enabling Standardization, Transparency, and Control - Purva Desai; Sahil Fruitwala (Emerging Frontiers Library for The American Journal of Applied Sciences, 2025)
Modern businesses increasingly rely on internal data products, such as curated datasets or analytical services, to drive innovation and informed decisions. Despite substantial investments in data technologies, including a global Artificial Intelligence market valued at 230 to 280 billion in 2024, large organizations struggle with inconsistent API interfaces. This inconsistency hinders efficient data exchange and robust governance. This paper tackles this challenge by proposing a framework for mandatory OpenAPI Specification (OAS) adoption and automated enforcement for all internal data products. Our approach defines clear organizational standards and implements a twostep compliance checking mechanism. This involves Static Type Analysis (STA) for foundational rule enforcement and an AI agent for nuanced, contextual validation. Integrated within CI/CD pipelines, this automated system ensures continuous adherence to design standards, enhancing data product discoverability, interoperability, and overall data governance. This work provides a practical methodology for establishing standardized control over internal data product APIs, streamlining development, and fostering a resilient data ecosystem.